Assessing the pH detection capabilities of polyaniline and composite materials involving reduced graphene oxide for salivary biosensing - Arveenamathii, Veeriah (2023)
Monitoring the pH levels in saliva within the oral cavity holds significant importance, serving as a valuable biomarker for prognosis and diagnosis, reflecting not only oral health but also various metabolic conditions. The lack of easily wearable intraoral pH sensors poses a significant challenge. This paper introduces a study involving the synthesis and assessment of conductive polymer polyaniline compounds for pH biosensing, with the aim of potentially developing intraoral biosensors for saliva analysis. Both reduced graphene oxide-polyaniline (rGO-PANI) and polyaniline (PANI) were employed as sensing materials to determine which material exhibited superior performance in pH biosensors. The study comprehensively evaluated these sensors, taking into account their sensitivity, repeatability, response time, stability, and pH range. Electrodeposition was employed to fabricate the sensors for both sensing materials. A comparative analysis of the performance of the two sensing materials was conducted using zero current potentiometry electrochemical analysis for the pH sensors. The analysis revealed that the rGO-PANI-based pH sensor performed better than the PANI-based pH sensor. These findings suggest that the rGO-PANI-based sensor could serve as a dependable tool for detecting pH variations in salivary analytes.